Mental health workers' values and their congruency with recovery principles. Issue 1 (9th January 2017) - Glajz, Bianca A.; Deane, Frank P.; Williams, Virginia
Abstract : Purpose: Recovery in mental health emphasises the empowerment of clients to discover and develop hope and a more satisfying life often in the presence of ongoing symptoms of mental illness. Work values that are incompatible with values that underpin the recovery philosophy may be contributing to the challenges in implementing recovery values in practice. The purpose of this paper is to explore the types of work values espoused by Australian mental health workers and their degree of congruence with recovery values. Design/methodology/approach: In total, 65 Australian mental health workers completed an open-ended work values question. Leximancer content analysis was used to generate a thematic work values profile followed by a theory-led thematic analysis of the responses to assess congruence with recovery values. Findings: This sample valued client-centred practice that supports recovery, making a difference in others' lives, work competence, being caring and empathic, and meaningful work. Overall, there was substantial congruence between work and recovery values, with less evidence of endorsement of values relating to strengths-based approaches, personal responsibility, and positive self-identity. These values should be targeted in future training initiatives. Originality/value: The current study is the first study to identify the types of work values espoused by Australian mental health workers and to examine the degree to which they are recovery-consistent. This is an important research agenda given the high national and international priority to adopt a recovery orientation, and the need to identify and modify potential barriers to the implementation of recovery-oriented services.